Thinking about Local Living Wage Requirements - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2002)
This paper reviews what we currently know about the benefits and costs of different varieties of a "living wage": a local government requirement, now adopted by over 50 local governments, for wages above the federal minimum imposed on employers with some financial link to the local government. The review includes economic theory, empirical research on local labor markets, and empirical research on the living wage. The paper concludes that moderate living wage requirements applied to the local government's own employees, and contractors' and grantees' employees who are funded by the local government, may do more good than harm. Excessive living wages or living wages applied to non-city funded workers are more likely to have negative side-effects. The merits of living wages applied to economic development assistance depend on the local economy's strength and whether this assistance program is used by the city's competitors. In a weak local economy, living wages applied to commonly-used economic development programs may reduce the city's economic growth.
Additional information: A revised version of this paper appears in Urban Affairs Review, Vol. 40, No. 2 (November 2004), pp. 269-299.
Keywords: J38; J45; J23; R23; R58; H72; 330; living wage; cities; Bartik